Hidden Carbenes: NHC-Al Species at the Al2O3–Ionic Liquid Interface - Qadir, Muhammad I.; Ebersol, Camila P.; da Silva, Blendo A.; Castegnaro, Marcus V.; Lião, Luciano M.; Sanches-Neto, Flávio O.; de Oliveira, Heibbe Cristhian B.; Pontes, Renato B.; Ebeling, Gunter; Dupont, Jairton (JACS Au, 2025)
The modification of the surface chemistry of heterogeneous catalysts/supports alters their electronic and catalytic properties, particularly through the incorporation of a monolayer of sophisticated N-heterocyclic carbenes (NHCs). However, the formation of aluminum N-heterocyclic carbene (NHC-Al) goes unrecognized or remains unidentified when imidazolium-based ionic liquids are supported on solids (SILPs). In this work, we identified the formation of NHC-Al species upon the grafting of imidazolium-based ILs onto neutral Al2O3. The optimal geometry of the imidazolium cations in these SILPs adopts a tilted orientation, exhibiting an upright binding mode, akin to self-assembled monolayers (SAMs). This configuration enables direct interaction of the electron-rich N–C–N moiety of the imidazolium cation with the Al2O3 surface, leading to the autocatalytic formation of NHC-Al species. The NHC-Al species are confirmed through solid-state 13C NMR, 13C–1H HETCOR, 27Al NMR, synchrotron XPS, XANES, and DFT calculations. This study provides unique insights into the bonding and structural geometry of ILs in SILPs, revealing features that have previously gone unobserved.